(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
It would not be an exaggeration to say that Ulukov Nasirjon Mukhammadalievich was one of the first in our country to work in depth on the topic of exotic vocabulary. The scientist defended his candidate’s thesis on the topic of exotic vocabulary in Uzbek religious texts. N. Ulukhov pays more attention to the religious units of exotic vocabulary than to the subject itself, and, generalizing the exotic vocabulary, defining mainly religious exotic words, says: "exoticisms are words that are used in Uzbek religious texts in their original form, preserving the religious, local, national spirit (color), and not being translated, which have no equivalent in our language."